2019
DOI: 10.1167/tvst.8.6.44
|View full text |Cite
|
Sign up to set email alerts
|

Residual Visual Responses in Patients With Retinitis Pigmentosa Revealed by Functional Magnetic Resonance Imaging

Abstract: PurposeWe evaluated the potential of magnetic resonance imaging in identifying signs of cortical visual processing with greater sensitivity than standard ophthalmological measures in patients with retinitis pigmentosa (RP) at advanced stages.MethodsEight patients affected with RP with only bare light perception and weak or absent visual evoked potential (VEP) or electroretinogram (ERG) responses to flashes of light were tested. Visual impairment was evaluated by means of psychophysical testing, where patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
(71 reference statements)
1
4
0
Order By: Relevance
“…In this study, we suggested that fMRI was a feasible method to objectively and quantitatively discriminate FP and NFP patients with advanced RP. An fMRI study has shown that severe impairment of RP had fewer V1 BOLD responses in contrast sensitivity visual tasks (Castaldi et al, 2019), another finding that was consistent with our study. However, due to the limited number of subjects, the study did not report a difference in different levels of patients with advanced RP, whereas our study showed that the response intensity of participants in the NFP group was significantly lower than that of participants in the FP group.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we suggested that fMRI was a feasible method to objectively and quantitatively discriminate FP and NFP patients with advanced RP. An fMRI study has shown that severe impairment of RP had fewer V1 BOLD responses in contrast sensitivity visual tasks (Castaldi et al, 2019), another finding that was consistent with our study. However, due to the limited number of subjects, the study did not report a difference in different levels of patients with advanced RP, whereas our study showed that the response intensity of participants in the NFP group was significantly lower than that of participants in the FP group.…”
Section: Discussionsupporting
confidence: 93%
“…Magnetic resonance imaging (MRI) affords the ability to obtain high resolution structural images of the visual cortex and also sensitively record associated responses (functional MRI). 122 Importantly, several MRI studies have described a degree of plasticity/remodelling following visual field defects in RCD or MD, and also with congenital visual impairment, including in ACHM. [123][124][125] The remapping of the primary visual cortex (V1) consists of a shift of central retinal inputs to more peripheral locations in V1, and this phenomenon was found to be larger in patients with more constricted visual fields.…”
Section: Neuroimagingmentioning
confidence: 99%
“…If melanopsin was sufficient for visual function under bright enough conditions, one would expect to have identified this phenomenon in certain individuals affected by various retinal pathologies, some of which largely spare ipRGC populations despite outer retinal degeneration ( Semo et al, 2003 ; Cui et al, 2015 ; Tran et al, 2019 ; Procyk et al, 2022 ). Although there is some evidence for residual melanopsin-mediated activity in such individuals ( Castaldi et al, 2019 ), it is unclear whether any of this activity can even be perceived. It seems more likely that melanopsin, rather than directly extending the dynamic range of the retina to extremely bright intensities, instead primarily mediates a range of functions that serve to accentuate and fine-tune certain aspects of pattern-forming vision.…”
Section: Discussionmentioning
confidence: 99%